Ideas previas en la Botánica - Mateos Jiménez, A. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1993)
We have found the same kind of botanical preconcepts among students of 8th EGB and students of theTeacher-training School from Toledo. if students have studied sciences the previous years these preconcepts seem less abundant. The most widespread is that pine -cone is the fruit of pir.es trees. Other beliefs are referred to flowers, trees, potatoes, fruits and seeds.